2022
DOI: 10.37213/cjal.2022.31626
|View full text |Cite
|
Sign up to set email alerts
|

Dual Language Books Go Digital: Storybooks Canada in French Immersion Schools and Homes

Abstract: In response to Canada’s growing ethnic, cultural, and linguistic diversity, educators in French immersion classrooms are increasingly responding with enhanced cross-linguistic initiatives, and dual language books are promising resources in the promotion of multilingualism (Zaidi, 2020; Zaidi & Dooley, 2021). This paper details a research project we completed in a 2019 classroom-based qualitative case study in a French immersion school experiencing an increasing enrollment of linguistically diverse students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
2
0
1
Order By: Relevance
“…This allows for accessing the same information through two different languages, and the reader can compare the story-either as a whole or at sentence/page level. Reading a story in a familiar language first allows for an overview and contextual understanding, while switching between languages at the sentence or page level affords contrasting of words and phrases [32].…”
Section: Bilingual and Multilingual Storiesmentioning
confidence: 99%
“…This allows for accessing the same information through two different languages, and the reader can compare the story-either as a whole or at sentence/page level. Reading a story in a familiar language first allows for an overview and contextual understanding, while switching between languages at the sentence or page level affords contrasting of words and phrases [32].…”
Section: Bilingual and Multilingual Storiesmentioning
confidence: 99%
“…Quelques recherches ont permis de documenter les effets de projets d'utilisation de ces albums auprès d'enfants et d'élèves bi/plurilingues (Gosselin-Lavoie, 2021 ; Naqvi et al, 2012 ;Zaidi, 2020), certaines dans une perspective de collaboration école-famille (Zaidi et al, 2022 ;Perregaux et Zurbriggen, 2012 ;Rodriguez-Valls, 2009). À notre connaissance, seule deux d'entre elles se sont centrées spécifiquement sur l'appréciation de l'expérience des parents.…”
Section: Les Approches Pédagogiques Inclusives Prenant Appui Sur La D...unclassified
“…Whereas in the past, FI teachers chose a monolingual, French, approach by monopolizing talk time, forbidding code-switching, and restricting group work options for example (Cummins, 2007). In recent years, there has been a shift in the traditional belief that a purely input-driven L2 learning experience is most effective, as advocated by proponents of FI programs (Cummins & Persad, 2014;Swain & Lapkin, 2013), to an increased focus on the examination of the role use a student's L1 can play in the language learning process (Davis et al, 2019;Fortune & Tedick, 2019;Mady, 2012;Mady & Garbati, 2014;Roy, 2015;Zaidi et al, 2022). Swain and Lapkin (2013) encouraged teachers to reflect on L1 use and to consider when and if its use supports student learning by facilitating comprehensible input.…”
Section: Changes In Pedagogy To Support the Recognition And Use Ofmentioning
confidence: 99%
“…Swain and Lapkin (2013) encouraged teachers to reflect on L1 use and to consider when and if its use supports student learning by facilitating comprehensible input. Zaidi et al (2022), conducted a case study whereby FI students from Grades K-6 were exposed to multilingual literacy teaching through the use of Storybooks Canada platform. Findings from this study revealed that the use of such multilingual tools enhanced student engagement in their respective multilingual contexts and reduced isolation of newly arrived students who were able to comprehend the stories that were being presented in their L1.…”
Section: Changes In Pedagogy To Support the Recognition And Use Ofmentioning
confidence: 99%